Tracing Scribal Variants and Textual Transmission: A Paleographic Approach to the Nanatsu-dera Manuscript of the Dafangguang Rulai Xingqi Weimizang Jing - Meiling Lin (Jianrong Shi) (Religions)
This paper examines the Nanatsu-dera manuscript of the Dafangguang Rulai Xingqi Weimizang Jing (RXWJ) through the lens of scribal practices, with a focus on variant characters (yitizi, 異體字) and textual transmission. As a “separately produced scripture” (bie sheng jing, 別生經), the RXWJ was not included in the woodblock-printed editions of the Chinese Buddhist canon, which limited its circulation and made manuscript copies—such as the Nanatsu-dera manuscript—critical for reconstructing its textual evolution, transmission, and scribal modifications. A detailed paleographic investigation reveals scribal variants, orthographic fluidity, and phonetic substitutions, illustrating both intentional adaptations and unintentional errors in textual transmission. Comparative analysis with Dunhuang fragments and the Taishō Canon further contextualizes these variations, shedding light on the interpretive challenges scribes and readers face. The findings suggest that the Nanatsu-dera manuscript underwent three stages of transmission: (1) it originated from the Fifty-Fascicle edition circulating in China, (2) it was used as a base text (diben, 底本) for manuscript copying in Japan, and (3) it was subsequently re-copied and preliminarily collated by Japanese scribes. By tracing scribal variants and textual transmission through a paleographic approach, this research underscores the critical role of manuscript culture in preserving texts outside the canonical tradition, offering new insights into the mechanisms of Buddhist textual transmission and adaptation in medieval East Asia.